2019
DOI: 10.1016/j.cej.2019.04.084
|View full text |Cite
|
Sign up to set email alerts
|

Studies on mass transfer of europium(III) in micro-channels using a micro Laser Induced Fluorescence technique

Abstract: The mass transfer of europium(III) from an aqueous to an organic phase was studied in a quartz microchannel (internal diameter of 200 μm) using a novel micro Laser Induced Fluorescence (micro-LIF) technique. Europium(III) was extracted from a 1M nitric acid solution into an organic solution of TBP(1.2M)/CMPO(0.2M) in Exxsol D80. For the flow rates investigated plug flow was established. An experimental and data processing methodology was developed to calculate concentration profiles from the fluorescing light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…Limited research has been reported by examining the supported liquid membranes 24 27 and microchannels to intensify the extraction process. 28 30 …”
Section: Introductionmentioning
confidence: 99%
“…Limited research has been reported by examining the supported liquid membranes 24 27 and microchannels to intensify the extraction process. 28 30 …”
Section: Introductionmentioning
confidence: 99%
“…Even though the increase in total flowrate resulted in higher specific interfacial areas due to smaller plug lengths, the plug formation time decreased, resulting in less contact time of the phases in the mixing zone. Previous studies have shown that the effect of mixing zone on the overall extraction efficiency of the reactor contributes from 25 to 40% depending mainly on the flowrate ratio, the total flowrates, and the channel size [ 13 , 16 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, for a constant flowrate, i.e., 1.6 mL/min, the extraction percentage increases 2.5 times when the channel size increases from 1 to 2 or 3.2 mm. This is mainly attributed to the fact that during plug flow, a large percentage (~35%) of mass transfer takes place during plug formation in the mixing zone [ 13 , 15 ]. It can also be seen that Ni(II) was not co-extracted in all cases, in agreement with the equilibrium results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations